Socio-Demographic and Economic Characteristics as Correlates of Work Attitudes of Elementary School Teachers - Bello, Mario M. (JPAIR Multidisciplinary Research, 2009)
The main objective of this study was to determine the work attitudes of the Katangawan Central Elementary School teachers as influenced by their socio-demographic and economic characteristics. Included as respondents in this study were 31 teachers from Katangawan Central Elementary School, Buayan District, General Santos City Division of School Year 2006 - 2007. The result showed that majority of the teachers belong to the 23 to 30 age bracket, non-Ilocano, females, single, and living in a rural area. Most of the teachers belong to the lowest salary level and have the least trainings too. Moreover, most of them have already taken some master's degree units. Thirty teachers have claimed that they are a member of a religious organization while one claims that he/she is not a member of any religious organization. As to the work attitudes of the teachers, they moderately agree that their work is a therapy and livelihood. The teachers disagreed that they do not look for other source of income aside from teaching. The teachers however agreed that their work is a service. It was revealed in this study that the socio demographic and economic characteristics of the teachers have no influence on their work attitude as a therapy, service and livelihood.
Keywords: Work attitudes; socio-demographic; economic; Katawangan Elementary School; teachers